2020
DOI: 10.1101/2020.01.09.900738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of a novel breathing circuit that controls pain and anxiety

Abstract: Alleviating pain with controlled breathing has been practiced throughout human history. Despite its wide use and long history, a neural circuit-based understanding of the pain-breathing interaction is largely lacking.Here we report a novel breathing circuit that regulates non-homeostatic breathing rhythm, as well as pain and anxiety. We identify that a cluster of neurons expressing the Oprm1 gene, which encodes the µ-opioid receptor (MOR) in the lateral subdivision of parabrachial nucleus (PBL Oprm1 ), directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…2 N and Q). The opposite effects on locomotion and calcium activity observed after morphine administration demonstrated that the breathing-associated fluctuation of PBL Oprm1 activity is not affected by the movement, which is further demonstrated in our concurrent independent study (39). In contrast, saline injection largely preserved the original patterns of the signals (Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…2 N and Q). The opposite effects on locomotion and calcium activity observed after morphine administration demonstrated that the breathing-associated fluctuation of PBL Oprm1 activity is not affected by the movement, which is further demonstrated in our concurrent independent study (39). In contrast, saline injection largely preserved the original patterns of the signals (Fig.…”
Section: Resultssupporting
confidence: 79%
“…In our view, OIRD is a synergistic outcome from impairment of the interconnected pontomedullary breathing network that widely expresses MOR both pre-and postsynaptically (15,16,35,51,52). For example, parabrachial neurons send tonic excitatory inputs to the preBötC (39,47,53,54), and both of these areas express MOR (23,55). Besides, the preBӧtC, as the breathing pattern generator, has been known to contribute to the OIRD phenotype, yet the level of its involvement varies across species and overdose models.…”
Section: Discussionmentioning
confidence: 97%
“…In our view, OIRD is a synergistic outcome from impairment of the interconnected pontomedullary breathing network that widely expresses MOR both pre-and post-synaptically (10,11,30,44,45). For example, parabrachial neurons send tonic excitatory inputs to the preBötC (39,43,46,47), and both of these areas express MOR (18,48).…”
Section: Investigating Oird With Cell-type-specific Approachesmentioning
confidence: 91%
“…Indeed, the incidence of OIRD is dramatically increased when opioids are used together with sedatives and anesthetics (52), and the failure to increase respiratory behavior in response to hypercapnic gas is one characteristic of OIRD (3). On the contrary, a mild inhibition of PBL Oprm1 neurons may explain many of the behavioral effects of lower doses of endogenous or exogenous opioids, such as slowed breathing, calmness, and reward (43). The current study used morphine as a starting point to induce OIRD, and further investigation is required to determine the involvement of PBL Oprm1 neurons under the challenge of other types of sedative agents.…”
Section: Pbl Oprm1 Neurons' Role In Breathing Regulation and Oirdmentioning
confidence: 97%
See 1 more Smart Citation